Establishing surface projection of Temporo- Mandibular Joint using tragus of ear as landmark - Prakash Baral; Janak Awasthi; Rami Shrestha; Subas Sapkota; Binod Chaudhari; Sapna Koju (Journal of Gandaki Medical College, 2020)
Introduction: The temporo-mandibular joint (TMJ) is a synovial joint between the articular fossa of the temporal bone and the mandibular condyle. It is condylar variety of joint. The most important functions of the TMJ are mastication and speech and are of great interest to anatomists, dentists, orthodontists and oro-maxillo-facial surgeons. The study was conducted with objective to establish the surface projection of Temporo-mandibular joint (TMJ) using tragus of ear as land mark.